Coupled Modified KP Hierarchy and Its Dispersionless Limit - Takebe, , Takashi; Teo, , Lee-Peng (2006)
We define the coupled modified KP hierarchy and its dispersionless limit. This integrable hierarchy is a generalization of the "half" of the Toda lattice hierarchy as well as an extension of the mKP hierarchy. The solutions are parametrized by a fibered flag manifold. The dispersionless counterpart interpolates several versions of dispersionless mKP hierarchy.